The effect of L-carnitine on growth performance and carcass characteristics of growing-finishing pigs - Owen, K.Q.; Smith, J.W. II; Friesen, K.G.; Blum, S.A.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ninety-six crossbred pigs (initially 75 lb BW) were used to investigate the effect of increasing dietary carnitine on growth performance and carcass characteristics in growing-finishing swine. Pigs (48 barrows and 48 gilts) were blocked by weight, ancestry, and sex in a randomized complete block design (two pigs per pen and eight pens per treatment). Dietary carnitine replaced cornstarch in the control diet to achieve added dietary carnitine levels of 25, 50, 75, 100, and 125 ppm. Grower (75 to 125 lb) and finisher (125 to 227 lb) diets were formulated to contain 1.0% lysine and .80%, respectively. All diets were corn-soybean meal-based, contained .15% L-lysine HCl and 2.5% soy oil, and were fed in meal form. When the mean weight for pigs in a pen reached 227 lb, one pig per pen was slaughtered to determine carcass characteristics. Dietary carnitine did not influence growth performance during the growing or finishing phases. However, for the overall trial, the mean of all pigs fed dietary carnitine had numerically improved average daily gain (ADG) and feed efficiency (F/G) when compared with pigs fed the control diet. Dietary carnitine reduced average backfat thickness and tenth rib backfat depth and increased longissimus muscle area, with 50 ppm providing the maximum response. These data suggest that 50 ppm L-carnitine fed during the growing-finishing phase had no effect on growth performance but resulted in increased muscle deposition and reduced fat accretion as measured by longissimus muscle area and average and tenth rib backfat depth.
Keywords: Swine; Growing-finishing; L-carnitine; Performance